Strengthening Brand Identity and Brand Communication on MSMEs in Increasing Competitiveness in the Digital Business Era - Krisnayanti Aditasari; Wahyu Eka Kiswardani; Hussein Gibreel Musa Salih; Jian Karisawati (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This community service program aimed to enhance the understanding and skills of MSME (Micro, Small, and Medium Enterprise) owners in developing brand identity and brand communication to improve business competitiveness in the digital business era. The program was conducted offline on June 12, 2026, at Telkom University Surabaya Campus and involved 25 MSMEs fostered by Telkom CDC Witel SBS. The methods employed included interactive workshops, hands-on practice, mentoring, and evaluation. The training materials covered the development of positioning and value propositions, tagline creation, marketing caption writing, storytelling techniques, and the utilization of digital media for business promotion. The results indicated an improvement in participants’ ability to build strong brand identities and develop more effective, persuasive, and consistent marketing communications. This program contributed positively to strengthening brand image and enhancing MSMEs’ readiness to compete in the era of business digital.